Personal Hygine dan infeksi cacing Enterobius vermicularis Pada Anak Usia Pra Sekolah - Indra Elisabet Lalangpuling; Pricilya Omega Manengal; Ketrina Konoralma (POLTEKKES KEMENKES MANADO, 2020)
Enterobiasis is a disease caused by worm infection Enterobius vermicularis that is commonly suffered by children. Transmission of Enterobius vermicularis is partly due to a lack of attention to personal hygiene. This research is descriptive in order to find out personal hygine and Enterobius vermicularis worm egg infection in pre-school children aged 3-6 years in the village Betelen 1, Southeast Minahasa Regency. The samples examined were 31 samples consisting of 3 years old children as much as 37%, 4 years as much as 29%, 5 years as much as 23% and 6 years as much as 10%. This research was conducted by taking primary data from observations and examinations using the method periplaswab. The results showed as many as 8 children (25.81%) positive found the worm eggs Enterobius vermicularis with behavior poor hygiene , as many as